Das tragédias íntimas às rupturas sociais: quando os amantes entram em cena no teatro de Nelson Rodrigues - Calixto, Thiago Guilherme (2022)
The tragedies of everyday life unveil the shadows that appear on the stages of the unconscious, which weave the psychic narratives from a dramatic body-text on which culture is inscribed. These discursive marks permeate the rodriguian theater, which goes through the reverse of morality, exposing the suburbs of morality, subverting social roles and making sacred the "sin" of sexual infidelity, as a constituent feature of modern drama. Thus, infidelity contrasts, in an antagonistic way, with its inverse, fidelity, a "dogmatic" premise historically built to regulate marriage, a religious civil institution, based almost entirely on the myth of monogamy. According to researchers Barash and Lipton (2007) there are strong indications not only social, subjective and contextual, but also biological, indications that human beings are not monogamous by nature, nor are the various other animal species close to being so. If, on the one hand, the ideal of romantic love becomes, fundamentally, the sustainer of these "fragile" modern matrimonial relationships, on the other hand, sexual fidelity, a moral demand inherent to these monogamous relationships, struggles not to succumb to the impetuosity of desire. In this way, the "symbiotic" connection between marriage and sexual fidelity often exposes how tenuous are the boundaries between desire and morality, thus demonstrating how precarious are the social ties that keep these customs standing. The psychoanalyst Haddad (2009), considers this constant tension a complex territory that often forms a tangle of meanings so distinct that they manage to overcome the moral precepts, laws and "good" customs, forging closer ties with the objects of desire. Freud (1930), on the other hand, delved into these tortuous instances, starting from primeval moments in which he found that such desires are drawn from a fantasized memory that refers to a temporal period in which there was a feeling of completeness that ceaselessly seeks to repeat itself, however, this return, inevitable, waives a whole load of suffering, originated by the loss of the objects of first love, which follow, and pursue, throughout life. Based on these findings, we sought to articulate an interweaving between psychoanalytic criticism and Brazilian literature. For this, we selected in Nelson Rodrigues' plays the corpus of this research, composed of a dramatic triad arranged according to the division formulated by Sábato Magaldi (1980), who proposed a thematic separation into three distinct levels of the seventeen rodriguianas plays: The Woman without Sin (1941): Psychological play; Family Album (1946): Mythical play and Every nudity will be punished (1965): Carioca tragedy. Thus, aiming to go through the nuances of the (in)faithful desire in the aesthetic construction of Rodrigo's drama, in which the roles attributed and self-conferred to the faithful, the unfaithful and the lovers, in the stages of immoralities, are immense in conflicts and social hindrances that surround the "domestic" tragedy of betrayal. Therefore, we will seek to discuss and establish interrelations between the objects of this desire and their fantasized (re)elaboration in the face of the uneasiness of infidelity. Finally, based on a wide theoretical background, we selected several works, including Freud (1905), Haddad (2009), Hubert (2013), Faust (2007), Castro (1992), Birman (2016), Ackerman (1997), among others.